Judiciary I Served - Reddy P. Jaganmohan (New Delhi)
This book is the detail of how repeated challenges, minor and major were thrown down at both state and central level, and how upright judges needed to struggle against such pressures in order to uphold the proper functioning of the law.
Keywords: Law